P-013 4 year review of radial access versus femoral access for diagnostic outpatient cerebral angiography: cost, length of stay, and complication rates. (22nd July 2018) - Satti, S; Reddy, P Krishna; Eden, T; Ansar, V
Abstract : Introduction: Radial access has been demonstrated to be associated with lower access site complications, greater patient satisfaction and cost savings for coronary angiography. We sought to assess whether radial access for outpatient cerebral angiography would result in lower length of stay (LOS) and, therefore, cost savings over femoral angiography. Incidence of major access complication rates (including transfusion and surgical vascular repair) was additionally reviewed. Methods: A single-center retrospective review of 101 consecutive radial access diagnostic cerebral angiogram via electronic database query in patients compared to 417 consecutive femoral access procedures. Using electronic query, LOS, patient demographics, procedure type, and complication rates were determined. Results: From January 2014 through February 2018, all patients undergoing out-patient cerebral angiography were identified and divided into femoral (417 pts-70% female) versus radial access (101 pts-75% female). Average age (years): 57 radial verus 56 femoral. Average procedure times: 41.6 min radial versus 54.5 min femoral. Average time in Interventional Suite: 7 min (9%) shorter with Radial. Average length of stay: 3.2 hours shorter LOS for radial access patients Radial: 6.8 hours (1% (1/111) required more than 12 hour stay – 12.8 hours) Femoral: 10.0 hours (6% (26/417) required required more than 12 hour stay-with an average of 32.8 hours in that subgroup) Major Complication Rates: 0% (no patients in either group required a transfusion or surgical vascular repair). Recovery Room Costs: 5% lower with Radial Access. Conclusion: Based on our single center retrospective review, incorporation of radial access for outpatient cerebral angiography is associated with shorter patient stays, lower cost, and no major complications. This time savings could increase case volume, while decreasing recovery room staffing. Disclosures: S. Satti: 2; C; Stryker Neurovascular, Penumbra Neurovascular. P. Krishna Reddy: None. T. Eden: None. V. Ansar: None.